Patellofemoral Joint Stress During Weight-Bearing and Non—Weight-Bearing Quadriceps Exercises - Powers, Christopher M.; Ho, Kai-Yu; Chen, Yu-Jen; Souza, Richard B.; Farrokhi, Shawn (The journal of orthopaedic and sports physical therapy, 2014)
Single-group, repeated-measures design. To compare patellofemoral joint (PFJ) stress among weight-bearing and non-weight-bearing quadriceps exercises. An important consideration when prescribing exercises to strengthen the quadriceps in persons with patellofemoral pain is to minimize PFJ loading. Currently, there is disagreement in the literature as to which exercises and ranges of motion best accomplish this goal. Ten healthy subjects participated. Lower extremity kinematics, kinetics, and electromyography of the knee musculature were obtained during a weight-bearing squatting exercise and 2 non-weight-bearing knee extension exercises: (1) knee extension with variable resistance, and (2) knee extension with constant resistance. A previously described biomechanical model was used to estimate PFJ stress at 0°, 15°, 30°, 45°, 60°, 75°, and 90° of knee flexion. PFJ stress was compared among the 3 exercises using a 2-way analysis of variance with repeated measures. Compared to the 2 non-weight-bearing exercises, the squat exercise produced significantly higher PFJ stress at 90°, 75°, and 60° of knee flexion. Conversely, the 2 non-weight-bearing exercises produced significantly higher PFJ stress at 30°, 15°, and 0° of knee flexion when compared to the squat exercise. The knee-extension-with-variable-resistance exercise produced significantly lower PFJ stress than the knee-extension-with-constant-resistance exercise at 90°, 75°, and 60° of knee flexion. To minimize PFJ stress while performing quadriceps exercises, our data suggest that the squat exercise should be performed from 45° to 0° of knee flexion and the knee-extension-with-variable-resistance exercise should be performed from 90° to 45° of knee flexion.